Pola Konsumsi Pangan Fungsional dan Formulasi Minuman Fungsional Instan Berbasis Antioksidan - Yuhlanny Dewi Suratno; Nurheni Sri Palupi; Made Astawan (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2014)
The objectives of this study were (1) to obtain the consumption behavior of functional food; (2) to develop the formulation of a functional drink product, and (3) to determine the nutrition fact of the best product prototype. The survey was conducted on 120 respondents, late 30 years old, to get a general view for product design. Respondents were grouped in four groups of age: 30-40 years (n=30), 41-50 years (n=30), 51-60 years (n=30) and older than 60 years (n=30). Each group consists of 15 men and 15 women. Six product prototypes were developed and evaluated by hedonic test (9 scales) and ANOVA test. Duncan’s test was used to select the best prototype. The result showed that Body Mass Index tend to increase at age 41-50 years olds. Metabolic syndrome becomes more prevalent and food consumption behavior changes from ‘free’ to ‘selected-consumption’ at age 51 years. Interest to purchase the functional food increases with age. Nutrition content/serving of the best prototype product were as follows: 2.5 mg iso avon, 2 g whey protein, 2.5 g fat, 5 g protein, 8 g carbohydrate, 720 ug total carotene (10% RDI), 68 mg vitamin C (75% RDI), 10 mg D-alpha tocopherol (80% RDI). The chosen product characterisitics include 6.5 ml solubility index, aw 0.46. Particle size is 99.14 μm. The nutritional claims of chosen prototype product are as follows: low fat, contains iso avone, whey protein and carotenoid, high content of vitamin C and E.